Prevalence of overweight/obesity and associated factors among under-five children in Ethiopia: A multilevel analysis of nationally representative sample - Gebremichael, Mathewos Alemu; Mengesha, Melkamu Merid; Hailegebreal, Samuel; Abdulkadir, Hanan; Arja, Asrat; Wolde, Biruk Bogale (Frontiers in Public Health, 2022)
Background: Childhood overweight and obesity are emerging public health challenges of the 21st century. There was a 24% increase in the number of overweight children under the age of five years in low-income countries. Despite the significant risk of childhood overweight/obesity for non-communicable diseases, premature death, disability, and reproductive disorders in their adult life, little attention has been given. Therefore, we aimed to assess the prevalence of overweight/obesity and associated factors among under-five children. Methods: This study was conducted using data from a nationally representative sample of the 2019 Ethiopia Mini Demographic and Health Survey (EMDHS). The Mini EDHS was a community-based cross-sectional study that covered all the administrative regions of Ethiopia. The data collection was conducted between March 21, 2019, to June 28, 2019. Both descriptive and analytic findings were produced using STATA version 14. For associated factors, a multilevel binary logistic regression model was fitted to account for the hierarchical nature of the data. Adjusted odds ratio (aOR) with 95% confidence interval (CI) was reported to show the strength of association and statistical significance. Results: A total 5,164 under-five children were included in this study. The overall prevalence of overweight/obesity was 2.14 % (95% CI; 1.74-2.53) (more than two standard deviations (+2SD) above the median of the reference population) based on the body mass index (BMI) Z-score. The odds of overweight/obesity was higher among children aged less than 6 months (aOR= 5.19; 95%CI: 2.98-9.04), 6-24 months (aOR = 1.97; 95%CI: 1.18-3.29), delivered by caesarean section (aOR = 1.75; 95% CI: 1.84-3.65), living in Addis Ababa city (aOR = 2.16; 95%CI: 1.59-7.81), Oromia region (aOR = 1.93; 95CI: 1.71-5.24), having mothers with the age 40-49 years (aOR = 3.91; 95%CI: 1.90-16.92), uses traditional contraceptive methods (aOR = 2.63; 95%CI: 1.66-10.47), and households headed by male (aOR = 1.71; 95%CI: 1.84-3.48). Conclusion: This study showed that childhood overweight/obesity is the problem in Ethiopia. There was an interplay of several factors that affect childhood obesity including child factors, maternal socio-demography, and healthcare utilization, and geography . Therefore, strategies to reduce childhood overweight and obesity should consider a multitude of contributing factors.